ANÁLISE DAS POLÍTICAS PÚBLICAS PARA OS QUILOMBOLAS DE LIVRAMENTO-PB (REMUNOM, 2024)
ABSTRACTThe present study aims to understand the relationship between social movements inpublic policies present in the Residents' Association of the Quilombola Rural community ofAreias de Verão, Vila Teimosa and Sussuarana, in the municipality of Livramento-PB,through identification, knowledge, and applicability of the social movement. With thefollowing specific objectives: the importance of the social movement for the Livramentensecommunity; identify the social and political dimension of the movement; and finally, analyzethe social movement as a tool for understanding society's needs. From the perspective ofnature, the research is exploratory, as it seeks greater knowledge of the topic to be studied,making it visible, flexible and adaptable to changes, as well as descriptive, since it carries outdata collection, through standardized collection techniques, such as forms and questionnaires,for example. Having said that, this course conclusion work aims to provide an overview ofpublic policies and implementation in the quilombola community present in the municipalityof Livramento-PB, aiming at the implementation and construction with popular participationof all rights guaranteed by law.